The Blue Zones solution : eating and living like the world's healthiest people - Buettner, Dan (National Geographic, 2015)
"Buettner [proposes that you may] transform your health using smart eating and lifestyle habits gleaned from new research on the diets, eating habits, and lifestyle practices of the communities he's identified as 'Blue Zones'--those places with the world's longest-lived, and thus healthiest, people: [Ikaria, Greece; Okinawa, Japan; Sardinia, Italy; Loma Linda, California; and Nicoya Peninsula, Costa Rica]"-- Amazon.com.